FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI - Velia Velia Brigitta Angelina Siswanto; Hendra Wijaya (Universitas Katolik Widya Mandala Surabaya, 2021)
All financial performance that has been carried out by the company during a period will be accounted for at the end of the year by disclosing the company's financial statements. Financial reports will later become one of the most important bases in taking action for both external and internal parties of the company, so that the quality of the financial reports produced by the company must be guaranteed. The demand for companies to produce quality financial reports can be assisted by the application of conservatism accounting principles because business situation can change quickly and unexpectedly. This research was conducted with the intention of testing and analyzing the influence of selected factors on the application of accounting conservatism. This research will be carried out by using a quantitative approach and testing hypotheses. This study examines manufacturing companies listed on the IDX in the 2015-2019 period to become the object of research. All samples were taken by purposive sampling method. The results of the study were obtained from multiple linear regression analysis, where it can be concluded that the occurrence of information asymmetry and the presence of an analyst does not guarantee that the company will or will not apply accounting conservatism. However, the litigation risk that may be faced by a company can influence the company in deciding the use of accounting conservatism principles.